THE CONCEPT OF SOFTWARE FOR INDIVIDUAL COMMUNICATION DEVICES IN ANY SINGLE INFORMATION FIELD OF TECHNOLOGICAL PROCESSES AT THE AIRPORT - Тамаргазін, Олександр Анатолійович; Ліннік, Іван Іванович (Science-based technologies, 2019)
As part of the paradigms of the unified information field of technological processes at the airport, the concept of creating software for individual communication devices is considered. The peculiarity of this software is that with its help, officials perform several operations in parallel: use the available information resources of a single information field, communicate with subordinates and representatives of different services and enterprises that operate at this airport. The proposed concept makes it possible to implement the logic of servicing the users of a single information field of the airport within the framework of the open software, which makes it possible to increase the capacity of information resources, to deny access to new services without the need to upgrade communication devices and use them as modern gadgets. Classification of modules that are used in the construction of software communication devices proposed to carry out as follows: subscriber, information, interface, transport, functional. This classification made it possible to take into account the most complete logical possibilities of implementing a single information field in a modern airport. The study showed the possibility of using a hypothetical architecture of a single information space for technological processes at the airport as an instrument for the formation of requirements for the software of communication devices in order to obtain a set of individual requirements for the structural elements of the software of communication devices, that is, requirements that are able to ensure their effective functioning in a single information space to ensure technological processes at the airport in the process of management. For this purpose, a methodology was developed to assess the compliance of the specific implementation of the software module of communication devices with the system of requirements that are put forward to them by a single information space for providing technological processes at the airport.